Long-term unemployment and suicide: a systematic review and meta-analysis. - Allison Milner; Andrew Page; Anthony D LaMontagne (PLoS ONE, 2013)
Purpose There have been a number of reviews on the association+ between unemployment and suicide, but none have investigated how this relationship is influenced by duration of unemployment. Method A systematic review and meta-analysis was conducted of those studies that assessed duration of unemployment as a risk factor for suicide. Studies considered as eligible for inclusion were population-based cohort or case-control designs; population-based ecological designs, or hospital based clinical cohort or case-control designs published in the year 1980 or later. Results The review identified 16 eligible studies, out of a possible 10,358 articles resulting from a search of four databases: PubMed, Web of Knowledge, Scopus and Proquest. While all 16 studies measured unemployment duration in different ways, a common finding was that longer duration of unemployment was related to greater risk of suicide and suicide attempt. A random effects meta-analysis on a subsample of six cohort studies indicated that the pooled relative risk of suicide in relation to average follow-up time after unemployment was 1.70 (95% CI 1.22 to 2.18). However, results also suggested a possible habituation effect to unemployment over time, with the greatest risk of suicide occurring within five years of unemployment compared to the employed population (RR = 2.50, 95% CI 1.83 to 3.17). Relative risk appeared to decline in studies of those unemployed between 12 and 16 years compared to those currently employed (RR = 1.21, 95% CI 1.10 to 1.33). Conclusion Findings suggest that long-term unemployment is associated with greater incidence of suicide. Results of the meta-analysis suggest that risk is greatest in the first five years, and persists at a lower but elevated level up to 16 years after unemployment. These findings are limited by the paucity of data on this topic.